Scale-free fault-tolerant topology control algorithm in wireless sensor network with optimization of path energy consumption - Hao-ran LIU; Tao HAN; Ya-qian LI; Rong-rong YIN (Tongxin xuebao)
For the issue of path energy consumption produced in the process of transmitting data in large-scale sensor network, an optimization model of network path energy consumption based on the mode of multi-hop was established, and then the law of obtaining the value of the node degree that could minimize the energy consumption of network was deduced. According to the optimal value of nodes, the network topology was built based on a fitness model which could control the network average node degree, and a scale-free fault-tolerant topology control algorithm EETA(energy effi-ciency topology algorithm) having the characteristics that could minimize the path energy consumption was put forward. The dynamic performance analysis indicates the network topology which was generated based on this algorithm had the strong fault tolerant ability, because the node degree distribution follows the power-law. The simulation results show that the algorithm also reduces the path energy consumption in the network and then make the network energy-efficient.